KEBERADAAN ALAT BUKTI SAKSI DALAM PERKARA PERCERAIAN (Studi Penelitian pada Mahkamah Syar’iyah Jantho) - Amiruddin, A. Hamid Sarong, Syarifuddin Hasyim, (Jurnal Ilmu Hukum, 2014)
Abstract: The reasons for a divorce must be supported by evidences namely; letters, witnesses, judges’ assume, plea and swear. The evidencing in a divorce case has a legal basis. The research reveals that the legal sources putting burden of proof of on evidences in the divorce cases at Mahkamah Syar’iyah Jantho has not been unified in the one act of Religion Process Act, the judges make legal bases of proof with witnesses in the divorce cases from an priest opinion obtained from Qoran and hadiths of Prophet Muhammad Peace be Upon Him, the doctrine of jurists, R.Bg/HIR (civil process law), the Indonesian Civil Act, the Act Number 7, 1989 regarding Religion Court, governments regulation number 9, 1975 regarding the Implementation of the Act Number 1, 1974 regarding Marriage, the Compilation of Islamic Law and Jurisprudences. The evidencing by witnesses in divorce cases in the Court is a way to prove is very urgent, however the witnesses is not only the one evidence that can bind the judge in deciding the case. It is not all divorce reasons must be proved by witnesses but it can be proven by other evidences unless by the reason of syiqaq or the conflict that happens long lasting time. For the law makers might enact applying law or special guidance ruling substances and procedural laws applying in the court hence there is concrete law for judges in putting burden of proof in the divorce case that can be referred by justice seekers that is going to get divorced by the Religion Court/Mahkamah Syar’iyah. Key words: divorce, witness evidence, Mahkamah Syar’iyah. Abstrak: Alasan perceraian harus didukung dengan alat bukti yaitu alat bukti surat, saksi, persangkaan hakim, pengakuan dan sumpah. Pembuktian dalam perkara perceraian mempunyai landasan hukum. Hasil penelitian menunjukan bahwa landasan hukum pembuktian dalam perkara perceraian di Mahkamah Syar’iyah Jantho belum diunifikasikan dalam satu undang-undang tentang Hukum Acara Peradilan Agama/Mahkamah Syar’iyah, sehingga Majelis Hakim menjadikan landasan hukum pembuktian dengan alat bukti saksi dalam perkara perceraian dari pendapat para ulama yang digali dari al-Quran dan hadits nabi Muhammad SAW, pendapat pakar hukum, RBg/HIR, KUHPerdata, Undang-Undang Nomor 7 Tahun 1989 tentang Peradilan Agama, Peraturan Pemerintah Nomor 9 Tahun 1975 tentang Pelaksaan Undang-Undang Nomor 1 Tahun 1974, Kompilasi Hukum Islam serta Yurisprudensi. Pembuktian dengan alat bukti saksi dalam perkara perceraian di Mahkamah Syar’iyah Jantho merupakan cara pembuktian yang sangat penting, namun tidak semua alasan perceraian wajib dibuktikan dengan alat bukti saksi, melainkan dapat dibuktikan dengan alat bukti lainnya, kecuali perceraian dengan alasan syiqaq atau perselisihan terus menerus. Kepada pembuat undang-undang dapat menetapkan suatu undang-undang khusus yang mengatur tentang hukum formil dan materiil yang berlaku di lingkunan Peradilan Agama/Mahkamah Syar’iyah, sehingga terdapat suatu ketentuan yang konkrit bagi hakim dalam membebankan pembuktian terhadap perkara perceraian dan dapat dipedomani oleh masyarakat pencari keadilan yang ingin melakukan perceraian melalui Pengadilan Agama/Mahkamah Syar’iyah. Kata Kunci: Perceraian, Alat Bukti Saksi, Mahkamah Syar’iyah.